IT Infrastructure for Research and Teaching Combining an Online Lab, a UAV and Audio-Visual Communication - Volkert, Thomas; Simon, Tobias; Henke, Karsten; Ostendorff, Steffen (International Journal of Online and Biomedical Engineering (iJOE), 2013)
From previous experiences with student work, we figured out that an interesting real studying object highly motivates students to understand the theory by hands-on experiments. Based on our former work, this paper introduces a new concept, which combines three of our research topics to one complex infrastructure. We start with our existing online lab â??REALâ? and describe how it can be used in order to provide an experiment environment, which is available independent of laboratory opening times. Based on this, we explain how a new experimental platform can be integrated, which is focused on the stabilization of a gimbal-mounted UAV. In this context, different control techniques from different engineering disciplines such as control theory, fuzzy control, neuronal networks and reinforcement learning can be applied. Furthermore, we describe how the video conferencing tool â??Homer-Conferencingâ? can be used as audio-visual platform to coordinate experiments. This approach enables the teacher to give direct feedback to the students. In general, our approach is intended to provide a flexible infrastructure, which can also be used among different experiment locations.